Physiological taxonomy of willow species - dormancy, rooting of cuttings, reaction on auxins - Kefeli, Valentine; Lininger, Chris; Shultz, Ratty (İstanbul Kültür Üniversitesi, 2007)
Cuttings of six willow species were rooted in water (control) and after auxin (indole-3-acetic acid 150 mg/l) treatment. The intensity of the dormancy was determined by the following data: Root formation, shoot development, and reaction on auxin. Silky, weeping, and pussy willows do not have deep dormancy and were sensitive to auxin. The cuttings of purple, autumn and white willows were less active in the rooting process and less sensitive to auxin. These species do not open their buds in favorite laboratory conditions. These physiological characteristics – rooting, bud opening, and reaction to auxin could be used as taxonomic features for willow identification. The rooting of poplar was connected with the position of cutting on the mother plant. The highest intensity of rooting was specific for the basal part of the twig of poplar (Populus nigra).
Keywords: willow; poplar; dormancy; rooting; bud opening; tomurcuk açma; köklendirme; kavak; söğüt